Possible Ways to Develop Foreign Language Learners’ Critical Language Awareness: A Case Study - Vadai, Kata (Working Papers in Language Pedagogy, 2014)
The need to develop foreign language learners’ critical language awareness (CLA) has become a relevant issue, since these days we are exposed to countless messages via the media, the television and the internet, and it is often difficult to decide how trustworthy the information is, or to what extent and in what ways it is controlled. Socially distributed power relations, ideologically manipulated discourses are parts of our everyday life, and in most cases we do not even suspect that we are massively manipulated. In such circumstances, teachers, as far as it is possible, have to develop students’ awareness in order to make them conscious, responsible citizens who can respond appropriately to the manipulative attacks of society. I propose that by exposing students to ideologically loaded phenomena and texts it is possible to teach them to read between the lines. In other words, if students are acquainted with hidden traits of manipulative discourses, they can hopefully think about them critically later. The research described in this paper, and conducted at a Hungarian university, investigates the potentials for this development by applying various methods of Critical Discourse Analysis (CDA) during a critical awareness development training programme which, for the most part, focused on political text and talk. The results of the study show that involving students in consciousness raising exercises definitely have an empowering effect on their thinking. There is a clear difference in their recognition of ideologies and manipulation hidden in texts, as well as in the world around them. The evidence presented in the case study seems to prove that there is great potential for developing learners’ awareness and sensitivity in the intake and processing of manipulative discourses and events.